Guidelines for Development of Graduate Curriculum in Vocational Education for Human Resource Development - Mekarkakorn , Tawica (Dusit Thani College Journal, 2020)
This research objectives were 1) To survey the needs for further study in vocational education for human resource development and 2) To suggest guidelines for the development of graduate programs in Vocational Education for Human Resource Development. The research was survey research which there are 2 phases; phase 1, survey the need for further study. The population consisted of 1) teachers/personnel in vocational education, and 2) others working in related fields in Bangkok and surrounding vicinities, 507 people. The instruments used in the research included questionnaires. The data were analyzed using frequency mean and percentages. Phase 2, finding guidelines for curriculum development by the quantitative method, the population were several graduates, 20 people. Using the tool as a questionnaire, analyze data with mean and percentage. And using guideline for focus group discussion that comprising a representative group of graduates, graduate students, education professionals. The data were analyzed by content analysis. The study found that after-work graduate-level education and short-term courses are in demand. Related considerations are fees, location, courses, and availability. Furthermore, with the study identified needs for more flexibility, accessibility, and increased course credits, along with the need to develop processing, writing, research, creativity, and innovation skills to comply with the national strategy.